(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
As the age of an elderly person increases, all body functions decline, therefore they are also more susceptible to contracting non-communicable diseases. This decline causes them to become more vulnerable to various diseases, especially non-communicable diseases such as diabetes and hypertension. One approach that can be taken is through health screening to detect potential diseases early, implementing physical activities such as gymnastics specifically designed for the elderly, and in-depth education about diabetes and hypertension. The purpose of the intervention in this community service activity is to improve the health status of the elderly, as well as a form of real contribution in supporting the achievement of Sustainable Development Goals (SDGs), especially in the aspect of inclusive and sustainable health. The implementation of activities is designed using methods based on scientific steps, which include research stages such as diagnosing to identify problems, planning to design interventions, action for implementation, evaluation to assess effectiveness, and specifying learning to take lessons from the process that has been passed. Through this series of activities, it is hoped that positive behavioral changes can occur, both in the elderly and the nursing home administrators, so that they become more aware of the importance of maintaining health and understand how to prevent non-communicable diseases. This is expected to create an environment that supports the health of the elderly, and has a long-term impact on improving their quality of life. — Seiring dengan bertambahnya usia pada seseorang lansia maka semakin menurun segala fungsi tubuh oleh karena itu semakin rentan juga untuk terjangkit penyakit tidak menular. Penurunan ini menyebabkan mereka menjadi lebih rentan terhadap berbagai penyakit, terutama penyakit tidak menular seperti diabetes dan hipertensi. Salah satu pendekatan yang dapat dilakukan adalah melalui skrining kesehatan untuk mendeteksi dini potensi penyakit, pelaksanaan aktivitas fisik seperti senam yang dirancang khusus untuk lansia, serta edukasi mendalam mengenai diabetes dan hipertensi. Tujuan dari intervensi dalam kegiatan pengabdian masyarakat ini adalah untuk meningkatkan derajat kesehatan lansia, sekaligus menjadi bentuk kontribusi nyata dalam mendukung pencapaian Sustainable Development Goals (SDGs), khususnya pada aspek kesehatan yang inklusif dan berkelanjutan. Pelaksanaan kegiatan dirancang menggunakan metode berbasis langkah-langkah ilmiah, yang meliputi tahap research seperti diagnosing untuk mengidentifikasi masalah, planning untuk merancang intervensi, action untuk pelaksanaan, evaluation untuk menilai efektivitas, serta specifying learning untuk mengambil pembelajaran dari proses yang telah dilalui. Melalui rangkaian kegiatan ini, diharapkan dapat terjadi perubahan perilaku positif, baik pada lansia maupun para pengurus panti, sehingga mereka menjadi lebih sadar akan pentingnya menjaga kesehatan dan memahami cara pencegahan penyakit tidak menular. Hal ini diharapkan dapat menciptakan lingkungan yang mendukung kesehatan lansia, serta memberikan dampak jangka panjang bagi peningkatan kualitas hidup mereka.